Human Resources Management Based on Spirituality to Improve the Quality of Education in Islamic Educational Institutions - Abidin, Zainal; Qusairi, Ahmad; Mubarak, Fadhel; Harry, Musleh (Al-Hayat: Journal of Islamic Education, 2025)
This study investigates the role of spirituality-based human resource (HR) management in enhancing the quality of education in Islamic educational institutions, with a case study at MA Miftahul Ulum Probolinggo, East Java. Using a qualitative case study design, data were collected through in-depth interviews, observations, and document analysis from 15 informants, including the principal, teachers, and staff. Data were analysed using thematic content analysis following Miles and Huberman's model, meanwhile, for data validity through source triangulation and member checking. The findings reveal that integrating Islamic spiritual values such as sincerity (ikhlāṣ), honesty (ṣidq), and trustworthiness (amānah) into recruitment, training, and performance appraisal fosters a harmonious work culture, increases teacher motivation, and strengthens student discipline and moral character. This value-driven HR management approach is institutionalised through formal policies and daily routines, such as collective prayers and Qur'an study sessions, which enhance both professional commitment and organisational cohesion. The study contributes to the literature by offering a contextual model of Islamic HR management that operationalises spiritual values in managerial practices to achieve holistic educational outcomes. The findings are presented in line with the research objectives. First, regarding the role of management, the principal acted as a value-based leader and role model, embedding Islamic spiritual principles such as sincerity (ikhlāṣ), honesty (ṣidq), and trustworthiness (amānah) into recruitment, training, and performance appraisal. Second, concerning the application of management principles, formal policies and daily routines accommodate values, such as communal prayer, Quran study sessions, and ethics-oriented performance evaluations, which foster a harmonious work culture, increase teacher motivation, and enhance students' discipline and moral character. While limited to a single institution, this research provides a contextual model for integrating spirituality into HR management practices to improve educational quality in faith-based schools.